A healthy "Risaotto al pomidauro" for D'Annunzio's poisoned Italy (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2022)
The essays provides the edition of the Risaotto al pomidauro, an anonymous collection of lyrical texts published in the «Giornale di Roma illustrato» in october 1886. The short introduction reminds the readers the context of this satirical publication which proves to be the parody of the forthcoming, Pre-Raphaelite poem titled Isaotta Guttadauro by Gabriele D’Annunzio, who had anticipated parts of his new work in magazines. Contemporary writers witness that the authors of the Risaotto were two journalists and literary critics, Edoardo Scarfoglio and Giovanni Alfredo Cesareo: the brief commentary which follows the edition of the Risaotto, beyond suggesting the probable collaboration of Matilde Serao to the work, enlightens the links between the contents of the satire and the critical opinions expressed by Scarfoglio and Cesareo on D’Annunzio’s personality and literary achievements.
Keywords: Risaotto al pomidauro; Isaotta Guttadauro; Gabriele D'Annunzio; Edoardo Scarfoglio; Giovanni Alfredo Cesareo; Matilde Serao